Kelimpahan Ikan Karang Famili Chaetodontidae dan Kondisi Terumbu Karang di Perairan Pulau Talam, Tapanuli Tengah - Dwi Arya Winata; Syafruddin Nasution; Thamrin Thamrin (Pelantar Press, 2022)
The Chaetodontidae family fish is an indicator species because it has a close relationship with coral reefs based on a strong preference for coral stone as the main component of coral reefs. The existence of these fish can be used as a guide to assess and monitor the condition of coral reefs. This study was conducted in March 2022. The purpose of this study was to determine the abundance of reef fish of the Chaetodontidae family in the waters of Talam Island, to determine the condition of life coral cover and the relationship between the abundance of the Chaetodontidae family and coral cover. The method used in this study is a survey method. Data collection on reef fish of chaetodontidae family was carried out using the Underwater Visual Census (UVC) method and coral reefs condition data collection was done using the Line Intercept Transect (LIT) method. The results showed that the abundance of Chaetodontidae ranged from 710 to 1,430 individuals/ha with an average of 1,110 individuals/ha. The highest abundance of 1,430 individuals/ha at station III with a depth of 6 meters, while the lowest abundance was station II with a depth of 8 meters which was 710 individuals/ha. The percentage of life coral cover at each station ranged from 47.70% - 56.98%, 42.60% - 54.40% and 56.68% - 69.08%. Based on these percentages, the average percentage of life coral cover is 54.74% (good category), and there is a very strong relationship between life coral cover and the abundance of the Chaetodontidae family.